Captura de CO2 por medio de los líquidos iónicos conformados por los cationes [omim] y [hmmim] con los aniones [(PFBu)SO3] y [(PFOc)SO3] para disminución de gas de efecto invernadero (2022)
In the present degree work, a study of 4 ionic liquids (ILs) made up of two cations was carried out, which are 2,3-dimethyl-1-hexylimidazolium [hmmim] and 1-octyl-3-methylimidazolium [omim] and the anions are perfluorobutanesulfonate [(PFBu)SO3] and heptadecafluorooctanesulfonate [(PFOc)SO3, in order to evaluate the absorption capacity of said ILs with CO2 molecules. This in order to reduce carbon dioxide emissions that occur due to the transformation of fossil fuels, reaching almost 37,000 million tons per year, where China and the United States of America are the largest polluters, contributing 30.64% and 13.53%, respectively, of total global emissions.